Development and establishment of an individual aggressiveness test protocol in breeding does - Olivas, Irene; Simarro, Laura; Villagrá, Arantxa (World Rabbit Science Association, 2020)
The present work aims to define the optimal conditions to perform a resident-intruder test in individually housed breeding does as a measure of aggressiveness and describe the biological characteristics of aggressiveness in rabbit does: severity, frequency, duration and latency of aggressive events. Sixty-four nulliparous does at 90 d of age were used for this experiment, half (32 does) as residents and the rest as intruders, testing them once a week for 14 wk. The time and duration of each aggressive behaviour was recorded and analysed to assess the aforementioned measures. According to the results, and regarding the studied effects, the origin of the animals caused no effect, whereas the level of aggressiveness seemed to be clearly increased in weeks 3-7 of the experiment, when animals were 110-140 d of age. In conclusion, a resident-intruder test lasting 1 min is enough to assess individual aggressiveness in adult breeding does, the response of which evolves with age and repetition.